Nendo 10/10. - Schulze, Floyd E.; Klanten, Robert (Berlin : Gestalten, 2013)
Oki Sato founded nendo in Tokyo in 2002. Since then, it has become one of the most sought-after design studios worldwide. The name nendo is Japanese for modeling clay. It is indicative of the studio’s playful, yet rational approach. Nendo: 10/10 is a comprehensive monograph of the studio’s work. Each of the book’s ten chapters showcases one of nendo’s design principles. Chapters explore, for example, nendo’s compelling approach to multiplying, linking, concealing, balancing, magnifying, and folding. Featured projects include vibrant store concepts and mystically inspired exhibition spaces as well as sculptural furniture pieces, home accessories, and design objects. Nendo’s impressively clear, yet intriguingly sophisticated work not only represents the epitome of contemporary design from Japan, but also sets the tone for design’s future on the global scene.
boek